Prevention of Catheter Related Blood Stream Infection Using Heparin Plus Gentamicin Catheter Lock Solution in Comparison to Heparin Alone. A Randomized controlled study. - Shahbaz, Muhammad; Muhammad, Tufail; Umar, Muhammad (Pakistan Journal of Kidney Diseases, 2021)
Optimal survival and the quality of life of patients with end stage renal disease (ESRD) on long term hemodialysis (HD) is largely dependent upon the adequacy of dialysis through an appropriately placed and properly functioning permanent vascular access with minimal mechanical complications and infection rates. The objective of the study was to: compare the frequency of catheter related blood stream infection (CRBSI) episodes with heparin alone vs heparin in combination with gentamicin in patients of ESRD on HD. METHODOLOGY: A total of 110 patients fulfilling the selection criteria were enrolled in the study from nephrology ward of Allied Hospital, Faisalabad and randomly divided in two groups. In Group A, at the end of each HD session, each port of the catheter was filled with 5000 U/mL of unfractionated heparin solution according to the volume of the ports. In Group B dialysis catheter lumens were locked with gentamicin in addition to heparin at 5000 U/mL. The final concentration of gentamicin in the antibiotic lock solution was 5 mg/mL. RESULTS: Out of 110 cases (55 in each group), mean age was calculated as 48.75+13.57 and 49.95+15.73 years in Group-A and B respectively. Males representation was higher in both groups, 52.73%(n=29) in Group-A and 60%(n=33) in Group-B. CRBSI was significantly higher in Heparin alone group: 29.09%(n=16) in Group- A and 9.09%(n=5), p= 0.007. CONCLUSION: We conclude that combination of heparin and gentamicin as compared to heparin alone is better in prevention of CRBSI in patients being dialyzed through temporary venous catheter.